Injection of basic fibroblast growth factor for unilateral vocal cord paralysis*. (2nd September 2017) - Kanazawa, Takeharu; Kurakami, Kazuya; Kashima, Kazutaka; Konomi, Ujimoto; Komazawa, Daigo; Nakamura, Kazuhiro; Matsushima, Koji; Akagi, Yusuke; Misawa, Kiyoshi; Nishino, Hiroshi; Watanabe, Yusuke
Abstract: Objective: Unilateral vocal cord paralysis (UVCP) not only induces severe dysphonia, but aspiration as well. Although laryngeal framework surgery is usually performed to treat this condition, the procedure is not tolerated by some patients. In the previous study, basic fibroblast growth factor (bFGF) injections for vocal cord scarring and sulcus have been reported to provide favorable outcomes while being minimally invasive. In this study, the authors retrospectively investigated phonological outcomes after bFGF injection in patients with UVCP. Methods: This study was registered in University hospital Medical Information Network – Clinical Trials Registry (UMIN000019347). Nineteen patients with unilateral cord paralysis were treated with bFGF injection. The treatment regimen involved a single injection of 50 μg of bFGF into the muscle layer. More than six months after the injection, aerodynamic and acoustic outcomes were examined. Results: The voice handicap index, maximum phonation time, mean airflow rate, and pitch range improved significantly after injection of bFGF. No sex-related differences were observed in any phonological parameter. Conclusion: bFGF injection, an easy method and suitable as an office procedure, significantly improved the hoarseness caused by UVCP. It is expected to be widely adopted and effective adjunctive drugs, and procedures are anticipated to be developed.